2014
DOI: 10.1186/2045-4015-3-29
|View full text |Cite
|
Sign up to set email alerts
|

Multiple chronic disorders - health care system’s modern challenge in the Maccabi Health Care System

Abstract: BackgroundOne of the major challenges health care systems face in modern time is treating chronic disorders. In recent years, the increasing occurrence of multiple chronic disorders (MCC) in single individuals has compounded the complexity of health care. In 2008, it was estimated that worldwide as many as one quarter of the population between the ages of sixty five to sixty nine suffered from two or more chronic conditions and this prevalence rose with age. Clinical guidelines provide guidance for management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…It was also found that older people face greater health burdens caused by multiple chronic diseases (Arbelle et al . ). As older patients suffer from the discomforts brought about by symptoms, dysfunction related to physical activities and impaired cognitive and emotional functions in the acute phase; when they return to their communities, they are faced with the problem of long‐term control of their diseases (Nolte & McKee , Ryan et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was also found that older people face greater health burdens caused by multiple chronic diseases (Arbelle et al . ). As older patients suffer from the discomforts brought about by symptoms, dysfunction related to physical activities and impaired cognitive and emotional functions in the acute phase; when they return to their communities, they are faced with the problem of long‐term control of their diseases (Nolte & McKee , Ryan et al .…”
Section: Introductionmentioning
confidence: 97%
“…When the prevalence of chronic diseases increases, the hospitalisation rate of the older adults becomes 3Á6 times that of other age groups, and their hospitalisation cost is as much as one-third of the overall hospital costs, showing the important needs for continuity of care (CoC) in care for the older adults (Ministry of Health and Welfare, Taiwan 2014). It was also found that older people face greater health burdens caused by multiple chronic diseases (Arbelle et al 2014). As older patients suffer from the discomforts brought about by symptoms, dysfunction related to physical activities and impaired cognitive and emotional functions in the acute phase; when they return to their communities, they are faced with the problem of long-term control of their diseases (Nolte & McKee 2008, Ryan et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The issues of perspective and reporting by parents were discussed above, although these are not necessarily negatives. Second, children may have multiple health conditions (3840) and children with a health condition often have multiple functional limitations. (41, 42) For example, chronic physical conditions have been shown to be a significant risk factor for behavior problems,(43) and ADHD is often associated with anxiety/depression and problems with usual activities.…”
Section: Discussionmentioning
confidence: 99%
“…Screening, an important first step, helps identify persons who can benefit from targeted preventive and therapeutic services; and analysis of screening and process data across populations helps in developing targeted programs. Diabetes, for instance, is more prevalent among Arab Israelis [ 2 ]; and as shown in an article in this journal from Maccabi Healthcare Services, multiple chronic diseases are more prevalent among older and poorer Israelis [ 3 ]. Programs at the community and practice level are, and in the future should be targeted to, and tailored for, high risk groups.…”
Section: Commentarymentioning
confidence: 99%
“…In the 21 st century, there is a high and increasing prevalence of single and multiple chronic conditions in the populations of developed countries, including Israel [ 3 ]. It has been known for many years that patients with multiple chronic conditions account for a very large percentage of total health care costs [ 4 ], estimated to be as high as 75 percent of total costs in the United States (U.S.).…”
Section: Commentarymentioning
confidence: 99%